The Intertwining and Its Pretext Between the Stories of Solomon’s Copper Carafes and The City of Brass in Ancient Arabic Literature - Abboud, Saleh (Religions, 2025)
This article examines the intertextuality and shared origins of two prominent narratives in classical Arabic literature: the story of Solomon’s Copper Carafes and the tale of The City of Brass. Both narratives, which later appeared in combined form in Alf Laylah wa-Laylah (One Thousand and One Nights), are laden with religious and mythological motifs that reflect broader cultural and theological concerns in the medieval Islamic world. This study attempts to answer the following question: “What are the common motives and ideas between the stories of Solomon’s Copper Carafes and The City of Brass in ancient Arabic literature?” By analyzing these stories as they appear in key sources of classical Arabic prose, this study investigates their shared themes and explores their potential common origins predating their Arabic textual forms. This study analyzes selected classical Arabic sources to demonstrate the narrative relationship between The City of Brass and Solomon’s Copper Carafes. It argues that both stories share a common origin predating their Arabic textual transmission. From a literary perspective, the tales of The City of Brass and Solomon’s Copper Carafes are prime examples of Islamic religious fiction, skillfully employing narrative devices to spread Islamic principles and beliefs. The stories are consistent with the core beliefs of Islam since they emphasize austerity, the certainty of death, and the primacy of monotheism. From a religious perspective, the intertwined stories of The City of Copper and Solomon’s Copper Carafes in Alf Laylah wa-Laylah provide a powerful example of how Islamic stories are inherently consistent with Islamic morality and beliefs.